Wilson chiral perturbation theory for dynamical twisted mass fermions vs lattice data: a case study - Cichy, Krzysztof; Zafeiropoulos, Savvas (Computer physics communications, 2019)
We compute the low lying eigenvalues of the Hermitian Dirac operator in lattice QCD with Nf=2+1+1 twisted mass fermions. We discuss whether these eigenvalues are in the ϵ-regime or the p-regime of Wilson chiral perturbation theory (χPT) for twisted mass fermions. Reaching the deep ϵ-regime is practically unfeasible with presently typical simulation parameters, but still the few lowest eigenvalues of the employed ensemble evince some characteristic ϵ-regime features. With this conclusion in mind, we develop a fitting strategy to extract two low energy constants from analytical ϵ-regime predictions at a fixed index. Thus, we obtain results for the chiral condensate and the low energy constant W8. We also discuss how to improve both the theoretical calculation and the lattice computation.